Program Pendampingan Caregiver Formal dalam Pengenalan dan Tata Laksana Kegawatdaruratan Lansia - Debora, Oda; Anugrahanti, Wisoedhanie Widi; Handini, Febrina Secsaria (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Older people in nursing home can experience emergency condition due to trauma or non-trauma. Meanwhile, caregivers acted as first responder whom provide immediate assistance to reduce morbidity and mortality rates for the elderly in care. Furthermore, regularly documenting the examination results online will facilitate monitoring of the elderly's condition. Objective: This community service aims to educate and train caregivers to provide first aid in emergency situations, as well as the application of periodic documentation of elderly vital signs through website-based medical record. Method: This community service was implemented by the Community Service Team from STIKes Panti Waluya Malang and fully funded by the Ministry of Education, Culture, and Technology in the 2025 funding year at LKS-LU Pangesti Lawang, the partner in this activity was their 14 formal caregivers.  This activities was designed to be implemented in eight meetings to improve caregiver’s knowledge and skills. In order to improve caregiver’s knowledge, lecture, discussion, question and answer method was used. Meanwhile to improve caregiver’s skill, demonstration, and simulation methods was used. The community provider was use questionnaire to evaluate the knowledge, and observation sheet to evaluate caregiver’s skill. The pre and post-test score were calculated, and categorized using N-Gain score. Result: Based on the calculation of the pre- and post-test score, the average N-Gain was 0.81 (N-Gain >0.7) for the theory, so it can be concluded that this activity has high effectiveness in improving caregiver knowledge. In addition, the average N-Gain for BHD performance was 0.8 and the N-Gain for choking performance was 0.9. Both have N-Gain >0.7, which means this simulation activity has high effectiveness in improving caregiver skills. To support E-RM documentation, the service team designed a website-based elderly development record system at https://pangesti.mikspwm.com, which was tested using the Blackbox method.  Conclusion: Providing education on first aid for emergency situations in the elderly through lectures, question-and-answer sessions, and discussions can improve caregivers' knowledge. Demonstrations, including simulations and demonstrations, can improve caregiver skills.